2017
DOI: 10.1139/er-2016-0054
|View full text |Cite
|
Sign up to set email alerts
|

The ecological impacts of lakewater calcium decline on softwater boreal ecosystems

Abstract: In recent decades, marked declines in calcium (Ca) concentrations have been noted in many softwater boreal lakes, and are believed to be a long-term consequence of acid deposition as well as other stressors (such as timber harvesting). Reduced Ca availability may act as a potent environmental stressor. Investigations of the direct ecological impacts of lower Ca concentrations in freshwater systems have largely focused on Ca-rich members of the Cladocera; however, a growing body of work, spanning several scient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 135 publications
(169 reference statements)
0
33
1
Order By: Relevance
“…Observations of declining Ca concentrations since the 1970s in eastern North American and Scandinavian lakes have been attributed to decades of accelerated Ca leaching from catchment soils as a result of acidic deposition, and have stimulated research efforts into associated ecological implications using laboratory and field experiments, regional limnological surveys, modeling, and paleolimnology (reviewed in Jeziorski and Smol 2017). Early laboratorybased studies identified several large Cladocera (crustacean zooplankton) species as vulnerable to Ca decline, and a threshold response for Daphnia pulex was determined when Ca concentrations fell below 1.5 to 2.0 mg/L (Ashforth and Yan 2008).…”
Section: Paleolimnology Can Provide the Missing Long-term Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Observations of declining Ca concentrations since the 1970s in eastern North American and Scandinavian lakes have been attributed to decades of accelerated Ca leaching from catchment soils as a result of acidic deposition, and have stimulated research efforts into associated ecological implications using laboratory and field experiments, regional limnological surveys, modeling, and paleolimnology (reviewed in Jeziorski and Smol 2017). Early laboratorybased studies identified several large Cladocera (crustacean zooplankton) species as vulnerable to Ca decline, and a threshold response for Daphnia pulex was determined when Ca concentrations fell below 1.5 to 2.0 mg/L (Ashforth and Yan 2008).…”
Section: Paleolimnology Can Provide the Missing Long-term Perspectivementioning
confidence: 99%
“…Calcium decline is a recently identified stressor on aquatic ecosystems, and the cooperation of researchers using complementary approaches resulted in a rapid accumulation of critical knowledge into the issue in a relatively short period of time (Jeziorski and Smol 2017). The example of Ca decline research provides a useful model for how paleolimnological techniques can be seamlessly integrated with other methods of inquiry to generate novel insights, with important advantages from a paleo-ecotoxicological perspective.…”
Section: Paleolimnology Can Provide the Missing Long-term Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…A useful roadmap for what enhanced cooperation could look like can be found by examining recent investigations into the ecological effects of lake water Ca decline, a legacy of acid rain and logging in regions with Ca-poor soils. Observations of declining Ca concentrations since the 1970s in eastern North American and Scandinavian lakes have been attributed to decades of accelerated Ca leaching from catchment soils as a result of acidic deposition, and have stimulated research efforts into associated ecological implications using laboratory and field experiments, regional limnological surveys, modeling, and paleolimnology (reviewed in Jeziorski and Smol 2017). Early laboratorybased studies identified several large Cladocera (crustacean zooplankton) species as vulnerable to Ca decline, and a threshold response for Daphnia pulex was determined when Ca concentrations fell below 1.5 to 2.0 mg/L (Ashforth and Yan 2008).…”
Section: Paleolimnology Can Provide the Missing Long-term Perspectivementioning
confidence: 99%
“…A useful roadmap for what enhanced cooperation could look like can be found by examining recent investigations into the ecological effects of lake water Ca decline, a legacy of acid rain and logging in regions with Ca‐poor soils. Observations of declining Ca concentrations since the 1970s in eastern North American and Scandinavian lakes have been attributed to decades of accelerated Ca leaching from catchment soils as a result of acidic deposition, and have stimulated research efforts into associated ecological implications using laboratory and field experiments, regional limnological surveys, modeling, and paleolimnology (reviewed in Jeziorski and Smol ). Early laboratory‐based studies identified several large Cladocera (crustacean zooplankton) species as vulnerable to Ca decline, and a threshold response for Daphnia pulex was determined when Ca concentrations fell below 1.5 to 2.0 mg/L (Ashforth and Yan ).…”
mentioning
confidence: 99%